Sexual machismo and safe sex in men residents of Tijuana, Mexico - López-Sánchez, Ulises (2025)
Introduction: Sexual machismo is a term of interest in the Latin American context. It is considered a risk factor for the health of men and women. In this regard, it may be related to the adoption of risky sexual practices, directly and indirectly impacting sexual and reproductive health. Objective: to determine the relationship between sexual machismo and safe sex in men living in Tijuana, Mexico. Material and methods: A study with a cross-sectional, descriptive and correlational design. The sample consisted of 310 men living in Tijuana, Mexico. Mixed online sampling was carried out. The inclusion criteria were being 18 years of age or older and having had sexual relations in the last year. For data collection, a sociodemographic data sheet, the Sexual Machismo Scale (EMS-12) and the condom use and safe sex subscales were applied. Descriptive and analytical statistics were applied. Results: A relationship was found between sexual machismo and safe sex in men living in Tijuana, Mexico. Discussion: Sexual machismo is correlated with safe sex in this group of men, this finding suggests that the greater the sexual machismo, the lower the safe sex. This data is consistent with that reported in various studies reported in the literature. Conclusions: The findings suggest that the more sexual machismo there is, the less safe sex there will be.